Determination of the dynamic viscosity of transparent fluids by using dynamic light scattering. - Will, Stefan; Leipertz, Alfred (Applied Optics, 1993)
The application of dynamic light scattering to the determination of the dynamic viscosity of transparent liquids is shown by the use of low-power (10-mW) laser sources and a multiple-tau correlator. A novel data evaluation scheme is demonstrated by the application of a nonlinear fit to various intervals of lag times, which can detect relevant systematic errors. An appropriate experimental procedure permits results with good accuracy and precision for selected liquids.
Keywords: DYNAMIC LIGHT SCATTERING; TRANSPORT PROPERTIES; DYNAMIC VISCOSITY